[Rezension von: Yü, Dan, 1962-, Hrsg., Trans-Himalayan borderlands] - Pandey, Abhimanyu (European bulletin of Himalayan research, 2020)
Published in 2017, this volume, an anthology of twelve essays by Chinese, European and North American social scientists, is an inaugural, multinational, collaborative project run by the Center for Trans-Himalayan Studies (CTHS) at China’s Yunnan Minzu University (YMU). Its genealogy includes conferences and workshops held between 2013 and 2015 by The New School, The Yale Himalaya Initiative and lastly YMU. These events all explored new ground in Himalayan studies by focusing on connectivity, ...